An exploratory spatial analysis of household size from 2006 to 2010 in Nigeria (2019)
Large household size of more than 5 persons per household (POPFACT, 2017) can hinder the attainment of Sustainable Development Goals (SDGs) by creating an unnecessary burden on family and the nation. Existing studies on household size have focused more on its consequences with limited attention to its pattern and causes. In addition, the smaller spatial units have mostly been the focus of such analysis and where a national data was used, the set of predictors often identified were assumed to explain the variations in household size across the component units. Due to differences in socioeconomic characteristics of residents and government policies, one expects differential predictors of household size in a multi-ethnic and multicultural country like Nigeria. Using the 2011 household survey data from the National Demographic and Health Surveys (NDHS, 2011), Moran-I, spatial regression, and Pearson Product Moment Correlation were used to analyse the spatial dependency in household size with a view to identifying its spatiotemporal correlates and predictors. The Moran-I showed that states that are contiguous have similar or near similar household sizes. Polygamy (r = 0.723, P<0.05), food poverty (r = 0.478, P<0.05), absolute poverty (r = 0.506, P<0.05) and a dollar-per-day poverty (r = 0.503, P<0.05) had a positive relationship with household size. Conversely, percentage of people using family planning (r = -0.687, P<0.05), unemployment (r = -0.434, P<0.05), percentage of the literate (r = -0.537, P<0.05), and number of higher institutions (r = -0.558, P<0.05) had negative significant relationship with household size. Improved use of family planning, access to education and encouraging monogamy will help in reducing large family size in Nigeria.